Creating accessible science museums with user-activated environmental audio beacons (Ping!) - Landau S; Wiener W; Naghshineh K; Giusti E (Assistive Technology)
In 2003, Touch Graphics Company carried out research on a new invention that promises to improve accessibility to science museums for visitors who are visually impaired. The system, nicknamed Ping!, allows users to navigate an exhibit area, listen to audio descriptions, and interact with exhibits using a cell phone-based interface. The system relies on computer telephony, and it incorporates a network of wireless environmental audio beacons that can be triggered by users wishing to travel to destinations they choose. User testing indicates that the system is effective, both as a way-finding tool and as a means of providing accessible information on museum content. Follow-up development projects will determine if this approach can be successfully implemented in other settings and for other user populations.